Credit Constraints as a Barrier to Technology Adoption by the Poor : Lessons from South-Indian Small-Scale Fishery - Giné, Xavier (World Bank, Washington, DC, 2012)
It is generally recognized that the adoption of a new technology plays a fundamental role in the development process. However, the benefits from the introduction of the technology may be unevenly distributed among the population, especially if the markets do not function properly. While the microeconomic literature on technology adopted and diffusion focuses on "who" and "when," the macroeconomic literature has focused on the overall impact of globalization on inequality. In this paper the authors bring these two strands of the literature together by studying the diffusion of plastic reinforced fiber boats in a fishing village in Tamil Nadu and by analyzing the dynamics of income inequality during this process.